Analisis Keterampilan Literasi Matematis dalam Memecahkan Soal Cerita Statistika Ditinjau dari Adversity Quotient - Dewi Widya Astuti; Dina Prasetyawati; Nizaruddin Nizaruddin; Nur Asiyah (Journal on Education, 2024)
Adversity quotient functions as an indicator of an individual's fighting power in showing the extent to which they will try to overcome a problem. The aim of this research is to describe the mathematical literacy of vocational school students in solving statistics problems by considering the AQ factor. This research is a qualitative study involving one subject for each climber, camper and quitter personality type. Data collection was carried out through tests and the validity of the data was tested through triangulation with the interview method. The collected data is analyzed by reducing the data, presenting the data, and drawing conclusions based on the mathematical literacy indicators that have been determined. The research results show that students' mathematical literacy abilities are in accordance with their personality type, where the higher the student's fighting power (AQ), the better they are. mathematical literacy. Each subject is able to formulate mathematical situations and apply mathematical concepts. However, only climber type subjects are consistent in interpreting mathematical solutions as a whole, while camper type subjects are able to think but their conclusions are less precise, and quitter type subjects are unable to show a logical reasoning process or produce correct conclusions. Based on the results of this research, it is recommended that students and teachers can encourage the development of tenacity and a spirit of not giving up in solving mathematical problems.